ANALISIS KEEFEKTIFAN KALIMAT DALAM SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS NEGERI MEDAN - Icha Indah Wardani; Immanuel Siregar; Tri Wahyuni; Fitriani Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of effective sentences in scientific writing is essential for conveying ideas clearly and systematically. However, ineffective sentences are still frequently found in undergraduate thesis writing, reducing clarity and coherence. This study aimed to describe the use of effective sentences, identify dominant types of ineffective sentences, and analyze factors contributing to sentence ineffectiveness in theses written by Biology Education students at Universitas Negeri Medan. This research used a descriptive qualitative approach. Data were taken from four undergraduate theses and collected through documentation and note-taking techniques. The data were analyzed using content analysis involving data reduction, classification, presentation, and conclusion drawing. The results showed 24 ineffective sentences categorized into five types: word economy, structural balance, idea coherence, logical language use, and parallelism. Word economy was the most dominant 41.7%, while parallelism was the least frequent 4.2%. These findings indicate that students still need improvement in applying effective sentence principles in academic writing. Therefore, systematic language guidance and academic writing supervision are needed to improve students’ ability to produce clearer and more effective scientific writing.